EVALUASI DIRI SEKOLAH (EDS) PADA SEKOLAH MENENGAH PERTAMA NEGERI DI KECAMATAN BANTAN KABUPATEN BENGKALIS - Dian Ratna Suri; Isjoni Isjoni; Zulfan Saam (Jurnal Manajemen Pendidikan Penelitian Kualitatif, 2018)
This research generally aims to provide an overview of the implementation ofschool self-evaluation (EDS) at junior high schools in the District Bantan Bengkalis district.Based on the observation that researchers do, there are problems associated with theimplementation of the EDS program in some of the junior high school in sub Bantan: 1)Understanding teachers and parents will EDS program is still low due to lack of socialization; 2)Components of schools do not have the time to implement EDS EDS considered that the additionalburden of school; and 3) Charging EDS instruments are not in accordance with the existingconditions. This research uses evaluation methods Goal Attaiment developed by Tyler in 1950.The study was the evaluation study, the research describes the problems associated with theimplementation of school self-evaluation (EDS) in Junior High School District Bantan.Components that are evaluated include: Implementation of the EDS program, Constraints andchallenges in the implementation of EDS, and the impact of the implementation of the EDSprogram. Techniques and Procedures collection DataPada this research through the study ofdocuments, observation and interviews. Data and Data Sources, Data used in this study is aschematic, narrative, description and explanation of data from informants either orally or data inthe form of a written document. Factors driving the implementation of the EDS internally is (1)HR; (2) coordination between stakeholders; (3) communication and a sense of family amongthe school community, externally is the support of the Department of Education and Culture andthe motivation of LPMP. Internally inhibiting factor is (1) saturation with EDS instruments; (2)short time; (3) lack of understanding of teachers, externally are (1) changes in the system andEDS instruments and (2) the number of inquiries on the instrument. Impact of EDS amongothers (a) facilitate the school in making RKS / RKAS and (b), enables schools to identifydeficiencies, the excess will be the performance of the school, the strength of the school to bedeveloped as well as the challenges faced by the school. EDS benefits include (a) a school canhave a data base for the development and improvement of quality in the future, (b) the results ofEDS used the school to encourage schools to improve and enhance the quality and performanceof the school. Follow-up of the school is based on the results of EDS is the repair, improvementand development of appropriate school performance 8 SNP.